1997
DOI: 10.1038/sj.gt.3300433
|View full text |Cite
|
Sign up to set email alerts
|

H1 and HMG17 extracted from calf thymus nuclei are efficient DNA carriers in gene transfer

Abstract: In this article we describe the chromatographic separation further transfection-active proteins. The highest transfecof acid nuclear protein fractions which have previously tion activity was associated with H1 and another nonidentbeen shown to be active in DNA transfection experiments.ified protein showing a somewhat higher electrophoretic By combining anionic and cationic ion exchangers, we mobility than H1. We have also found that the presence of were able to separate and identify some of the active proCaCl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 5 publications
0
30
0
Order By: Relevance
“…The most active fractions identified contained histone H1 and the nonhistone protein HMG17. The nonhistone proteins HMG1 and HMG2 also may have a role as DNA carriers for gene transfer (11). Other investigators claim that histone H3 and H4 are effective in gene delivery of the HIV-1 tat gene in Jurkat cells (15); neither histone H1 nor histone H2A were effective in this study.…”
mentioning
confidence: 40%
See 2 more Smart Citations
“…The most active fractions identified contained histone H1 and the nonhistone protein HMG17. The nonhistone proteins HMG1 and HMG2 also may have a role as DNA carriers for gene transfer (11). Other investigators claim that histone H3 and H4 are effective in gene delivery of the HIV-1 tat gene in Jurkat cells (15); neither histone H1 nor histone H2A were effective in this study.…”
mentioning
confidence: 40%
“…Peptides corresponding to consecutive regions of charged amino acids peptides 10, 12, 13, and 16 were synthesized, and peptide 10, corresponding to residues 1-36 of histone H2A, was found to be active. Peptides that subdivided this N-terminal region (peptides [11][12][13][14] or fused it with the C terminus (peptide 17) had background levels of transfection activity. Similarly, peptide chimeras of the Nterminal portion of peptide 10 fused with sequences from H2B, H3, and H4 (peptides 27-29) lacked significant transfection activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Foreign gene expression was also improved by other DNAbinding proteins, but the greatest enhancement was obtained with the complexes that contain either NLS-H1 or calf thymus histone H1 (Fritz et al, 1996). In digitoninpermeabilized or cytosol-microinjected cells, H1 histone is imported in the cell nucleus by a facilitated transport mechanism (Breeuwer and Goldfarb, 1990;Kurz et al, 1997), and has been shown to be an efficient transfection agent, when used with a low calcium or chloroquine concentration (Chen et al, 1994;Fritz et al, 1996;Zaitsev et al, 1997;Böttger et al, 1998). Furthermore, Chen et al (1994) have developed a novel DNA delivery system to accomplish gene transfer through the asialoglycoprotein receptor-mediated endocytosis pathway.…”
Section: Histonesmentioning
confidence: 99%
“…In vivo experiments performed with liposomes/HVJ/HMG-1 complexes also revealed an efficient gene transfer in the liver (Kato et al, 1991;Tomita et al, 1992;Namiki et al, 1998). HMG1/2 or HMG17 complexes extracted from the calf thymus nuclei were also shown to be efficient DNA carriers in gene transfer (Zaitsev et al, 1997).…”
Section: Hmg-box Proteinmentioning
confidence: 99%